Social Innovations in Urban Sanitation in India Meeting Unmet Needs - Dasgupta, Shubhagato (Taylor & Francis, 2023)
This book discusses effective social innovation strategies facilitated by civil society organisations (CSOs) to tackle India's significant urban sanitation challenge. It presents the contours of an ecosystem that includes citizen participation and strengthening community-managed systems for improved sanitation and public health. The book analyses case studies of effective sanitation programmes as well as experiments with innovative ideas in different regional contexts by CSOs to meet the contextual needs of the community and to ensure access to safe sanitation, especially among the urban poor. It highlights the challenges and the need for active participation of communities for change in behaviour, increasing institutional capacities of municipalities for standardising and scaling up strategies which work. The authors highlight the need for designing low-cost solutions, organising informal sanitation workers, serving marginalised communities and building effective alliances between communities and institutions to influence public policy. Rich in empirical data, this book will be useful for scholars and researchers of urban studies, public policy, governance, political science, development studies and sociology as well as for CSOs and non-governmental organisations (NGOs) working on urban sanitation, urban planning and public policy.